150 years since the birthday of therapist, professor Nikolai Nikolevich Dyakov - A. V. Andreeva; U. N. Grin'kova; I. M. Kobelev; G. O. Samburov; G. B. Chetskaya (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Of great importance for the history of medicine is the coverage of the life path of people who left a bright mark on the history of the Fatherland, contributing to the development of the medical field. This article is dedicated to one of such people – Professor Nikolai Nikolaevich Dyakov (1875—1954) in honor of the 150th anniversary of his birth, who during his life lived through several wars, a change of power in the country and many other famous historical events. Archival documents, scientific literature, books and articles served as materials for the study. The life story of N.N. Dyakov is amazing in that, being the son of a sailor, he became a doctor of medical sciences, professor and headed the departments of medical institutes for more than 20 years. The last position he held was the head of the department of hospital therapy at the Arkhangelsk State Medical Institute from 1936 to 1953. For half a century of impeccable work in the field of public health, for the good organization of the scientific, pedagogical and medical process at the department, he was awarded the Order of Lenin. The professor's scientific works were devoted to the study of the medicinal properties of birch bark, wild rosemary, the development of methods for treating alimentary dystrophy, vitamin deficiencies, the study of the therapeutic factors of mineral waters and northern resorts, the study of the effect of ascorbic acid isolated from pine needles on the treatment of patients with vitamin deficiencies, etc. Nikolai Nikolaevich Dyakov is a bright representative of the northern scientific school, an experienced therapist who enjoyed authority among colleagues and the population of the Arkhangelsk region, whose life story deserves coverage.